2021
DOI: 10.1177/20543581211041184
|View full text |Cite
|
Sign up to set email alerts
|

T Scores, FRAX, Frailty Phenotype, Falls, and Its Relationship to Fractures in Patients on Maintenance Hemodialysis

Abstract: Background: Despite the magnitude of fracture and the consequences in patients receiving hemodialysis, optimal risk assessment tools in this population are not well explored. Frailty and falls—known risk factors for fracture in chronic kidney disease (CKD) and non-CKD populations—are common in patients receiving hemodialysis (HD) therapy. While the relationship between T scores in relation to fractures in patients receiving HD is recognized, there is a paucity of data to the additional contributions of fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, in the multivariate analysis, only steroid use was found to be significantly associated with prevalent VFs (OR 0.121, 0.015–0.988), with lumbar BMD being marginally statistically significant ( P = .051). Gogas Yavuz et al [ 49 ] reported femoral neck BMD (Z-score) to be a risk factor for VF development in kidney recipients, while another study reported each lower −1 SD in femoral neck T-score to be associated with 48% higher odds of fracture (OR 1.48; 1.20–1.68, P = .005) [ 71 ]. Although an association has been reported between aortic and iliac calcifications and VFs, potentially due to the role of vitamin K deficiency in both bone and vascular pathology [ 44 ], other authors have not observed a significant association [ 46 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…However, in the multivariate analysis, only steroid use was found to be significantly associated with prevalent VFs (OR 0.121, 0.015–0.988), with lumbar BMD being marginally statistically significant ( P = .051). Gogas Yavuz et al [ 49 ] reported femoral neck BMD (Z-score) to be a risk factor for VF development in kidney recipients, while another study reported each lower −1 SD in femoral neck T-score to be associated with 48% higher odds of fracture (OR 1.48; 1.20–1.68, P = .005) [ 71 ]. Although an association has been reported between aortic and iliac calcifications and VFs, potentially due to the role of vitamin K deficiency in both bone and vascular pathology [ 44 ], other authors have not observed a significant association [ 46 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies in patients with CKD consistently show that lumbar spine T-scores are higher than the femoral neck, suggesting that patients receiving dialysis disproportionately lose bone mass at the femoral neck. 7,10,11 While it is possible some of this discrepancy may be due falsely high measurements at the spine due to extraskeletal calcification, a recent cohort of patients receiving haemodialysis showed that lumbar spine BMD was not significantly higher in those with abdominal aortic calcification compared to those without. 12 Another possible explanation for the differences across sites is the classic densitometric feature of hyperparathyroidism which disproportionately affects cortical compared to trabecular bone.…”
Section: Does Bmd Predict Fracture Risk In Patients Receiving Pd?mentioning
confidence: 99%
“…19 Small studies show it performs reasonably well in those receiving haemodialysis, although the evidence as to whether its addition to BMD improves prediction is mixed. 11,20 FRAX may be a helpful adjunct in guiding if a patient should be treated, both in those with low BMD, or those with a suspicion for increased fracture risk despite relatively preserved BMD.…”
Section: Can We Improve the Predictive Power Of Bmd?mentioning
confidence: 99%